Land-use intensification systematically alters the size structure of aquatic communities in the Neotropics - Collyer, Giovanna; Perkins, Daniel M.; Petsch, Danielle K.; Siqueira, Tadeu [UNESP]; Saito, Victor (Wiley, 2023)
Land-use and land-cover transitions can affect biodiversity and ecosystem functioning in a myriad of ways, including how energy is transferred within food-webs. Size spectra (i.e. relationships between body size and biomass or abundance) provide a means to assess how food-webs respond to environmental stressors by depicting how energy is transferred from small to larger organisms. Here, we investigated changes in the size spectrum of aquatic macroinvertebrates along a broad land-use intensification gradient (from Atlantic Forest to mechanized agriculture) in 30 Brazilian streams. We expected to find a steeper size spectrum slope and lower total biomass in more disturbed streams due to higher energetic expenditure in physiologically stressful conditions, which has a disproportionate impact on large individuals. As expected, we found that more disturbed streams had fewer small organisms than pristine forest streams, but, surprisingly, they had shallower size spectrum slopes, which indicates that energy might be transferred more efficiently in disturbed streams. Disturbed streams were also less taxonomically diverse, suggesting that the potentially higher energy transfer in these webs might be channelled via a few efficient trophic links. However, because total biomass was higher in pristine streams, these sites still supported a greater number of larger organisms and longer food chains (i.e. larger size range). Our results indicate that land-use intensification decreases ecosystem stability and enhances vulnerability to population extinctions by reducing the possible energetic pathways while enhancing efficiency between the remaining food-web linkages. Our study represents a step forward in understanding how land-use intensification affects trophic interactions and ecosystem functioning in aquatic systems.
Keywords: aquatic insects; benthic macroinvertebrates; energy transfer; food-web; freshwater ecosystems; individual size distributions; land-use intensification; length–mass equation; macroecology; metabolic theory